The Impact of ChatGPT Technological Innovation on Civil Law Practices: Challenges, Opportunities, and Implications of Article 1338 of the Civil Code - Purba, Yuspika Yuliana; Silalahi, Johan Alfred Sarades (CV Firmos, 2024)
In the continuously evolving digital era, technological innovation increasingly influences various aspects of human life, including civil law practices. One intriguing technological innovation is ChatGPT, an artificial intelligence-based language model capable of generating high-quality text closely resembling human capability. This research aims to provide a deeper understanding of the impact of ChatGPT technological innovation on civil law practices, considering the challenges, opportunities, and implications of Article 1338 of the Civil Code. This study is a literature review employing a qualitative approach and descriptive analysis. Data for this research were gathered from Google Scholar within the timeframe of 2019-2024. The study's findings indicate that the introduction of technological innovations such as ChatGPT has significantly transformed the landscape of civil law practices. Despite posing several challenges, such as technological skill availability, data security, and questions regarding legal validity, ChatGPT also presents substantial opportunities to enhance efficiency and accessibility in civil law practices. Considering the legal principles underpinning civil law practices, particularly within the context of Article 1338 of the Civil Code, is crucial in evaluating the impact and utilization of technologies like ChatGPT. The necessity for collaboration between legal experts and technologists to develop guidelines and standards that guide the ethical and effective use of technology is also highly imperative.